Analyzing Skill Development in the Context of Automotive Digital Transformation - Krishna Prasad Buravelli, Srinivasa (Digital Repository of Theses - SSBM Geneva, 2024)
The automotive sector, especially in places like India, is at a turning point in its digital evolution due to changing consumer needs and rapid technical breakthroughs. To address the growing skill gap impeding the sector's digital transformation, this shift calls for a careful assessment of employee’s capabilities and a reassessment of conventional business strategies. With an emphasis on the significance of technical competences and proactive adaptation in Industry 4.0, the study attempts to explore how the industry's digital transformation affects employee proactive skill development. The researcher used a mixed method using semi structured interviews for collecting qualitative data through and purposive sampling, and random sampling for quantitative data collection, to look into the complex relationship between proactive skill development and industry-level digital strategy maturity in the automotive sector. This methodology improves the validity and dependability of our results by identifying subtle differences in skill dynamics in the context of digital transformation. Using partial least squares structural equation modelling (PLS-SEM), the study came up with a way to show how the maturity of an industry's digital strategy affects proactive skill development through digital transformation. The findings emphasized how digital strategy maturity influences skill development through the mediating effects of digital adoption urgency, familiarity, feasibility, and complexity. It has become clear that proactive employee involvement is necessary for successfully managing these partnerships. The suggestions include developing proactive cultures and putting in place continuous education initiatives to close the skills gaps in digital literacy, cybersecurity, artificial intelligence, and data analytics. Taking into account the moderating influence of proactive personality qualities on employee impressions of digitization, the study highlights the necessity of customised methods in digital transformation initiatives. Future studies should look into the long-term effects of digital skill development programmes on organisational performance, how company culture affects attitudes towards digital transformation, how digitalization affects automotive supply chains, how different digitalization strategies perform across national borders, and how ethical considerations arise from digital transformation in the automotive industry.